MnO2@Fe3O4 Magnetic Nanoparticles as Efficient and Recyclable Heterogeneous Catalyst for Benzylic sp(3) C-H Oxidation - Pandey, Akanksha M.; Agalave, Sandip G.; Vinod, Chathakudath P.; Gnanaprakasam, Boopathy (Chemistry-An Asian Journal, 2019)
Herein, we report a highly chemoselective and efficient heterogeneous MnO2@Fe3O4 MNP catalyst for the oxidation of benzylic sp(3) C-H group of ethers using TBHP as a green oxidant to afford ester derivatives in high yield under batch/continuous flow module. This catalyst was also effective for the benzylic sp(3) C-H group of methylene derivatives to furnish the ketone in high yield which can be easily integrated into continuous flow condition for scale up. The catalyst is fully characterized by spectroscopic techniques and it was found that 0.424 % MnO2@Fe3O4 catalyzes the reaction; the magnetic nanoparticles of this catalyst could be easily recovered from the reaction mixture. The recovered catalyst was recycled for twelve cycles without any loss of the catalytic activity. The advantages of MnO2@Fe3O4 MNP are its catalytic activity, easy preparation, recovery, and recyclability, gram scale synthesis with a TOF of up to 14.93 h(-1) and low metal leaching during the reaction.

Catalyst-assisted selective vinylation and methylallylation of a quaternary carbon center using tert-butyl acetate - Mohanta, Nirmala; Samal, Pragnya Paramita; Pandey, Akanksha M.; Mondal, Shankhajit; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2023)
The In-(OTf)(3)-catalyzed & alpha;-vinylationof varioushydroxy-functionalized quaternary carbon centers using in situ generatedisobutylene from tert-butyl acetate is presentedas a novel synthetic methodology. Moreover, tert-butylacetate is a nonflammable feed stock and is a readily available sourcefor the in situ production of vinyl substituents, as demonstratedby the vinylation reaction with quaternary hydroxy/methoxy compounds.Moreover, an excellent selectivity for methylallylation over vinylationwas obtained with Ni-(OTf)(2) as a catalyst. In the case ofperoxyoxindole, methylallyl-functionalized 1,4-benzoxazin-3-one derivativeswere formed through the sequential rearrangement of peroxyoxindolefollowed by the nucleophilic attack by isobutylene. The detailed mechanismfor this reaction and rationalization for the selectivity are providedusing kinetics and density functional theory studies.